Post traumatic schwannoma over right temporo-zygomatic region: a case report - Gandhi, Yash A.; Hirani, Narendra; Sorathiya, Rashmi D.; Khilnani, Ajeet Kumar; Shah, Dhruvin; Chandra, Mridima (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2024)
Schwannomas are benign tumour. Post traumatic schwannoma over head and neck region is a rare entity. The occurrence of head and neck schwannomas is approximately 25-50%. The most common site of occurrence of schwannoma in head and neck region is found to be lateral part of neck. Schwannoma is a radio-resistant tumour. Complete surgical excision is the definitive management. The characteristic histopathological finding in Schwannoma is Antoni A area and Antoni B area of cellularity and Verocay bodies. We report a rare case of post traumatic schwannoma over right temporo-zygomatic region in an 18-year-old female.